Pengaruh Inquiry Terbimbing Berbantuan Augmented Reality Flashcards pada Peningkatan Literasi Sains Siswa Sekolah Dasar dalam Materi Tata Surya - Muhammad Jagad Chakim; Widiyono, Aan; Muzakki, Muhammad Alie (Lembaga Bale Literasi, 2025)
Science literacy skills involve the application of science, the ability to recognize problems, and draw logical conclusions through existing data that need to be instilled since elementary school. Guided inquiry is an alternative learning approach that has proven effective in encouraging students' science literacy, especially in studying the topic of the solar system. This study examines the effect of guided inquiry assisted by augmented reality flashcards to encourage the improvement of science literacy in students at the primary education level. This research design applies a pre-experimental one-group pre-test-post-test because there is only one rombel at SDN 02 Kedung Jepara, with 24 grade VI students as samples. Research instruments in the form of pre-test and post-test using 16 multiple choice questions that have been tested for validity and reliability. Based on the results of the Paired Samples T-Test test, there is a significant difference in pretest and posttest scores, indicated by an average value of -21.61458 and the acquisition of significance results (Sig. 2-tailed) 0.000. The increase in the average score from 57 to 79 confirms that guided inquiry has an effect in improving science literacy.